2001
DOI: 10.1007/s001670000189
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularisation in Achilles tendons with painful tendinosis but not in normal tendons: an ultrasonographic investigation

Abstract: Chronic Achilles tendinosis is a condition with unknown aetiology and pathogenesis, most often, but not always, associated with painful nodular thickening of the tendon. In this investigation, 28 tendons (21 patients) with a painful nodule located at the 2-6 cm level in the tendon, and 20 normal (pain-free) tendons, were examined with grey-scale ultrasonography combined with colour Doppler examination. In all tendons with a painful nodule, but not in any of the normal pain-free tendons, neovascularisation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
379
7
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(413 citation statements)
references
References 31 publications
16
379
7
11
Order By: Relevance
“…24,25 The absence of demonstrable vascularity on color Doppler imaging in healthy tendons is consistent with previous studies. 9,10,26 In current practice, there are several sonographic findings that may suggest a diagnosis of tendinopathy, including increase in tendon caliber, altered fibrillar echotexture, and increased tendon vascularity. 8,9 In our study, tendinopathic tendons were significantly larger than normal controls at the midportion of the tendon and at the calcaneal insertion.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The absence of demonstrable vascularity on color Doppler imaging in healthy tendons is consistent with previous studies. 9,10,26 In current practice, there are several sonographic findings that may suggest a diagnosis of tendinopathy, including increase in tendon caliber, altered fibrillar echotexture, and increased tendon vascularity. 8,9 In our study, tendinopathic tendons were significantly larger than normal controls at the midportion of the tendon and at the calcaneal insertion.…”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why the hypovascularization derives from stress. Despite this, many studies have shown that degenerative tendon disorders mainly develop in the region where the tendon has a poor or no blood supply: poor vascularization or avascularity are believed either directly to decrease tensile strength or indirectly to weaken the tendon through degenerative changes, hence increasing the likelihood of rupture (hypothesis of hypovascularization) [28,[66][67][68][69][70][71] . They are suggested to be important risk factors also for chronic tendinopathy (high intratendinous lactate levels, indicating ischemic conditions, where found in chronic Achilles tendinosis [72] ) especially in the way they influence tendons' metabolism and healing mechanisms.…”
Section: Extrinsic Risk Factorsmentioning
confidence: 99%
“…Åström and Westlin (1994b) found even blood distribution in the Achilles tendon, with a decrease seen at the insertion. It has also been shown that injured Achilles tendons have an increased blood flow in the symptomatic area compared with controls (Åström and Westlin, 1994a, Öhberg et al, 2001, Knobloch et al, 2006. Despite differences in findings regarding the blood flow to the Achilles tendon, there appears to be a consensus that there are reductions in the blood flow with increasing age (Tuite et al, 1997, Langberg et al, 2001a.…”
Section: Circulationmentioning
confidence: 99%
“…It has also been suggested that reduced blood circulation causes impaired metabolic activity and disturbed oxygen transport and is therefore detrimental to the tissue repair (Tuite et al, 1997, Kannus, 1997a. This is, however, controversial and several research reports suggest that there is no reduction in blood supply to the midportion of the tendon (Åström and Westlin, 1994a, Öhberg et al, 2001, Knobloch et al, 2006.…”
Section: Pathogenesis -The Development Of a Diseased Or Morbid Conditionmentioning
confidence: 99%